Unveiling the Rainbow in Sri Lanka’s Troubled Landscape: A Critical Assessment of Legal Recognition of Homosexual Rights in Sri Lanka - Gamage, T.G.G.; Perera, L.A.R.R. (University of Colombo, 2024)
It has been proven that the denial of recognition of one’s right leads to the negation of its existence itself. Over countless centuries, individuals within the LGBTQ community have faced relentless deprivation of their inherent rights, from street mistreatments to being disowned by their own kin. Regrettably, these prejudices, often supported by certain religious beliefs and irrational theories devoid of logical foundations, persist prominently in the South Asian Region. In this context, despite Sri Lanka’s recent attempts at decriminalizing homosexuality within its borders, doubts arise about whether such amendments would provide the legal recognition that these individuals truly deserve. Amidst this backdrop, this paper evaluates the effectiveness of the contemporary legal landscape concerning the rights of homosexuals in Sri Lanka, assessing whether these amendments strike a balance between the ‘protection of LGBTQ Rights against discrimination’ and the equally essential dimension of ‘respecting and accepting them’. Key findings indicate that while legal protections have been implemented, they fall short of fostering true social integration and dignity for the LGBTQ community. By delving into historical records, legal advancements and seminal legal cases, this paper charts the transformative journey of legal recognition for homosexual rights...
Keywords: Homosexual Rights; Decriminalizing Homosexuality; LGBTQ Rights in Sri Lanka; Human Rights; Equality